Rights of Persons with Disabilities in Nigeria - Etieyibo, Edwin (Afrika Focus, 2020)
This paper employs the conceptual-analytical method to analyse literature and news reports on disabilities, and international legal documents and instruments on human rights and the rights of persons with disabilities to which Nigeria is a signatory. This study is conducted in the context of exclusionary and discriminatory practices against persons with disabilities in Nigeria. The practices and rights that are examined are in the areas of education and accessibility with regard to adults and children with disabilities, work and employment, and the employment or use of children with disabilities in alms-soliciting. The paper’s broad objective in critically discussing these practices is to make a case for why and how they violate the rights of persons with disabilities. KEY WORDS: DISCRIMINATORY PRACTICES, DISABILITY, HUMAN RIGHTS, NIGERIA, PERSONS WITH DISABILITIES, RIGHTS